Detection of occult invasion in ductal carcinoma in situ of the breast with sentinel node metastasis - Osako, Tomo; Iwase, Takuji; Kimura, Kiyomi; Horii, Rie; Akiyama, Futoshi (Cancer science, 2013)
By definition, ductal carcinoma in situ (DCIS) – pre‐invasive breast cancer – does not metastasize to the lymph nodes. However, since the introduction of molecular whole‐node analysis using the one‐step nucleic acid amplification assay for sentinel node (SN) biopsies, the number of patients with DCIS and SN metastasis has increased. The pathogenesis and clinical management of DCIS with SN metastasis remain controversial. In this case–control study, in order to elucidate the pathogenesis of SN metastasis in DCIS, we compared occult invasions between the SN‐positive and SN‐negative DCIS and investigated predictive factors of occult invasion. The subjects were 24 patients selected from 285 patients with a routine postoperative diagnosis of DCIS who had undergone SN biopsy using the one‐step nucleic acid amplification whole‐node assay between 2009 and 2011. Of these 24 patients, 12 were SN‐positive, and 12 were SN‐negative. The 12 SN‐negative patients make up the control group and were selected from the 273 SN‐negative patients based on patient characteristics. All paraffin blocks of the primary tumor from each patient were step‐sectioned with 500‐μm intervals until the block was exhausted and histopathologically examined. We analyzed 1830 step‐sectioned slides and found occult invasions were more frequent in the SN‐positive group (7/12, 58.3%) than in the SN‐negative group (3/12, 25.0%). All occult invasions were <5 mm. There was no correlation between occult invasion and SN tumor burden, non‐SN metastasis, or patient characteristics. Our results suggest true metastasis from occult invasion may be a potent pathogenesis indicating nodal metastasis in postoperatively diagnosed DCIS. Patient follow‐up is required to elucidate the prognostic impact of nodal metastasis and occult invasion.